Comparison of unfractionated heparin and fondaparinux in relation to the incidence of recurrent myocardial infarction - Suryoputri, Masita Wulandari; Astuti, Dwi Aprilia; Endriastuti, Nialiana Endah; Ilma, Dewi Latifatul (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Acute Myocardial Infarction (AMI) is a cardiovascular condition that involves necrosis of the heart muscle because of a decrease in blood supply to the heart caused by an obstruction of the coronary arteries. The prevalence of cardiac disease is 1.5% including AMI, and ranked 4th above all provinces in Indonesia. Anticoagulants are administered for the management of AMI treatment. Anticoagulants are treatments utilized to prevent thrombosis and reduce ischemic injury, preventing hemorrhage from developing in the heart's arteries and veins. Unfractionated heparin (UFH) and fondaparinux are both anticoagulants, that are utilized frequently in the treatment of AMI-EST patients. In decreasing the production of thrombin and preventing coagulation, unfractionated heparin, and fondaparinux can avoid death and recurrent myocardial infarction. The research was conducted as an observational study with retrospective data collection from medical records of inpatients diagnosed with acute transmural myocardial infarction of the anterior wall at Prof. Dr. Margono Soekarjo Purwokerto from January 2019 to December 2021. The chi-square test was used to examine the association between the type of anticoagulant therapy (unfractionated heparin or fondaparinux) and the incidence of recurrent myocardial infarction. The statistical analysis showed a significant association between the type of anticoagulant therapy and the incidence of recurrent myocardial infarction (p < 0.05). A higher proportion of patients treated with fondaparinux did not experience recurrent myocardial infarction compared to those treated with unfractionated heparin, suggesting that fondaparinux may be more effective in preventing recurrence.